The temporomandibular opening index in patients with temporomandibular disorders undergoing surgical extraction of mandibular third molars : A pilot study - (:unkn) unknown (My University, 2006)
Amaç: Bu çalışmanın amacı alt üçüncü büyük azı dişlerinin cerrahi çekiminin temporomandibular rahatsızlığı olan olgularda temporomandibular açılma indeksine etkisini araştırmaktır. Gereç ve Yöntem: Alt üçüncü büyük azı dişlerinin cerrahi çekimi gereken temporomandibular rahatsızlığı olan 10 hasta (2 erkek, 8 kadın; 21 ile 33 yaşları arasında) bu çalışmaya alınmıştır. Cerrahi çekimden önce ve cerrahi çekimden 3 ay sonra bu hastaların stomatolojik muayeneleri ve temporomandibular açılma indeksleri aynı hekim tarafından yapılmıştır. Temporomandibular açılma indeksi şu formülle tayin edilmiştir: Passive opening (mm) – Maximum voluntary opening (mm) TOI = ----------------------------------------------------- x 100 Passive opening (mm) + Maximum voluntary opening (mm) Bulgular: Cerrahi çekimden 3 ay sonra temporamandibular rahatsızlığın semptomlarında ve temporomandibular açıklık indeksinde anlamlı bir azalma görülmüştür. Sonuç: Temporomandibular açılma indeksi mandibular hareketlerinin sınırlı olduğu durumlarda iyi bir değerlendirme kriteri olarak kullanılabilir.

Objective: The aim of this study was to examine the effect of surgical extraction of impacted mandibular on the Temporomandibular Opening Index (TOI) in patients with temporomandibular disorders (TMD). Materials and methods: Ten patients (2 males, 8 females; age range 21 to 33 years) with TMD undergoing surgical extraction of the impacted third molars were recruited in this study. Before the surgical operation and three months after the surgical operation the clinical stomatognathic examinations were carried out by the same dentist, specialized in the stomatognathic physiology, who also determined TOI (in percents) according to the following formula: Passive opening (mm) – Maximum voluntary opening (mm) TOI = ----------------------------------------------------- x 100 Passive opening (mm) + Maximum voluntary opening (mm) Results: Three months after surgery, a marked improvement in signs and symptoms of TMD, as well as a statistically significant (p <0.01) decrease in TOI was observed. Conclusion: The TOI seemed to be a good assessment criterion of limitation in mandibular mobility.
Alt üçüncü büyük azı dişlerinin cerrahi çekimi gereken temporomandibular rahatsızlığı olan olgularda temporomandibular açılma indeksi: Ön calışma
Keywords: Cerrahi